Pencatatan dan Pelaporan Keuangan dengan Zahir Accounting pada UMKM “Green Laundry” - Tiska Ayu Mahardika; Nonny Laurencia Nawangsari; Dian Puspitasari; Vieka Maharani Firdaus; Niken Fitriani (P3M Politeknik Negeri Malang, 2023)
The purpose of financial recording and reporting activities using Zahir software for MSMEs is to provide a solution for MSMEs, namely Green Laundry in Penjaringan Sari, Surabaya City so that they can process financial data properly using Zahir software. This can improve the performance and productivity of MSMEs, especially in terms of management and accountable financial management. This activity is a form of our dedication to the community to apply the knowledge we have acquired in the Accounting study program, UPN Veterans Jawa Timur. This is related to the problem that there are still many MSMEs that do not realize the importance of well-organized financial records and bookkeeping. Through this activity, it is hoped that it can help MSME entrepreneurs to realize that well-organized financial records and bookkeeping are important. This activity was carried out through three stages, starting with the identification of several MSMEs, then collecting data, and finally recording and reporting finances. The results of this activity are financial reports, namely income statements, balance sheets, and cash flow statements.